Research of ECMS Energy Management Strategy of Hybrid System based on Grey Forecasting - Deng Tao; Cheng Dong; Zhou Hao; Wang Mingming (Jixie chuandong)
To further improve the fuel economy and online real-time optimization ability of energy management strategy for Hybrid Electric Vehicle（HEV）,the grey forecasting GM（1,1） model is established to forecast real-time vehicle speed,and then combined with Equivalent Consumption Minimization Strategy（ECMS） to be proposed HEV ECMS energy management strategy with grey forecasting method.Furthermore,the entire HEV simulation model is built,and the three different WVUCITY,WVUSUB and WVUINTER cycle is selected to simulate and analyze the effect of energy management.The simulation results show that,firstly,the precision of grey forecasting for speed is reliable.Secondly,the SOC will be more stable and battery has longer life by integrating grey forecasting and ECMS.Finally,the fuel economy is increased by 7.4%,7.5%,6.3%respectively through the proposed strategy,when compared with the non-forecasting method under the above three cycle.